Phytotea “ATINE” enhances the immunomodulatory effect of adaptogenic factors of the Truskavets’ Spa in patients after radical treatment of oncological pathology - Bombushkar, Igor; Korda, Mykhaylo; Gozhenko, Anatoliy; Savytskyi, Ivan; Chebanenko, Oleksandr; Badiuk, Nataliya; Zukow, Walery; Anchev, Anatoliy; Duzhar, Viktor; Popovych, Dariya; Popovych, Igor (Journal of Education, Health and Sport, 2025)
Background. The beneficial effect of balneofactors of the Truskavets’ Spa on the immune status of patients with various chronic diseases is well known. On the other hand, a similar immunomodulatory effect is exerted by various medicinal plants. Based on this, we set ourselves the goal of clarifying the possibility of enhancing the immunotropic effect of balneofactors by combining them with medicinal plants. Material and methods. The subjects of the study were 52 patients aged 44÷75 years (36 women aged 59.3±9.3 years and 16 men aged 60.0±8.3 years), who came for rehabilitation at the Truskavets' Spa after radical treatment of oncopathology. The state of cellular, humoral and phagocytic links of immunity was assessed using routine methods, and two equal groups were formed on this basis. Members of the control group received standard balneotherapy for two weeks, while the main group additionally consumed the newly created herbal tea “ATINE”. Results. Supplementing standard balneotherapy with phytotea “ATINE” significantly modulated its immunotropic effects. First, “ATINE” neutralized the balneotherapy-induced decrease in IgG levels, reversed the tendency to decrease neutrophils content into an increasing trend, initiated an increase in CIC and T-killer levels, as well as enhanced the activating effect of balneotherapy on the level of natural killer cells. Secondly, “ATINE” leveled the balneotherapy-induced increase in the absolute content of B-lymphocytes and IgA in the blood, initiated a decrease in the absolute content of pan-lymphocytes and T-helpers, and deepened the balneotherapy-induced decrease in the relative content of T-helpers and IgM. However, the additional use of “ATINE” did not affect the balneotherapy-induced increase in the bactericidal ability of blood neutrophils and its factors (activity, intensity and completeness of phagocytosis of the Staph. aureus strain), the absolute content of natural killers and the relative content of B-lymphocytes, the reaction of blast transformation of T-lymphocytes to PHA, as well as the entropy of the immunocytogram. Conclusion. Phytotea “ATINE” enhances the immunomodulatory effect of adaptogenic factors of the Truskavets’ spa in patients after radical treatment of oncological pathology. Based on the analysis of the research document on "ATINE" herbal tea used in patients after radical oncological treatment at the Truskavets Spa, the following conclusions supported by mathematical analysis can be drawn. 1. "ATINE" herbal tea significantly increases NK and T-killer cell levels. Mathematical confirmation: NK cell level increase: standard balneotherapy effect was +0.51±0.09 (p<0.05), while with additional "ATINE" it increased to +0.97±0.10 (p<0.05); "ATINE" effect alone: +0.46±0.10; T-killer level increase: standard balneotherapy +0.05±0.56 (non-significant), with "ATINE" +1.36±0.46 (p<0.05); "ATINE" effect alone on T-killers: +1.31±0.51; Discriminant analysis confirmed these effects with r*=0.654; Wilks' Λ=0.547; χ²(12)=60; p<10⁻⁶. 2. "ATINE" modulates immune response by decreasing T-helper and IgM levels. Mathematical confirmation: T-helper level decrease: standard balneotherapy -0.54±0.28 (non-significant), with "ATINE" -1.16±0.23 (p<0.05); "ATINE" effect alone on T-helpers: -0.62±0.26; IgM level decrease: standard balneotherapy -1.47±0.28 (p<0.05), with "ATINE" -2.59±0.44 (p<0.05); "ATINE" effect alone on IgM: -1.12±0.36; Regression analysis showed strong correlation between T-killer and T-helper level changes: R=0.909; R²=0.826; p<10⁻⁶. 3. "ATINE" increases circulating immune complexes (CIC) without affecting neutrophil bactericidal capacity. Mathematical confirmation: CIC level change: standard balneotherapy -0.12±0.30 (non-significant), with "ATINE" +0.77±0.34 (p<0.05); "ATINE" effect alone on CIC: +0.89±0.32; No difference in neutrophil bactericidal capacity (BCCN): standard balneotherapy +1.10±0.58, with "ATINE" +1.06±0.35 (p<0.05); t-value for effect comparison: 0.00 (complete absence of difference); Mahalanobis distances between groups confirm significant differences between baseline and both therapies (p<10⁻⁶), as well as between standard balneotherapy and therapy with "ATINE" (p=0.075).